2021
DOI: 10.1007/s13318-020-00668-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of COVID-19 on Cytochrome P450-Mediated Drug Metabolism and Disposition in Infected Patients

Abstract: Coronavirus Disease 2019 (COVID-19) has been a global health crisis since it was first identified in December 2019. In addition to fever, cough, headache, and shortness of breath, an intense increase in immune response-based inflammation has been the hallmark of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) virus infection. This narrative review summarizes and critiques pathophysiology of COVID-19 and its plausible effects on drug metabolism and disposition. The release of inflammatory cytokines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 106 publications
4
48
0
Order By: Relevance
“…Accordingly, it cannot be excluded that DDIs predicted to be moderate in SARS-CoV-2-uninfected patients might eventually become clinically relevant in some phases of the COVID-19 disease. Indeed, during the active phase of SARS-CoV-2 infection, pro-inflammatory cytokines are likely to downregulate the activity of liver enzymes, eventually counterbalancing the well-known inductive effect of corticosteroids on drug metabolism [ 9 ]. However, when the inflammatory phase ends, corticosteroid-related DDIs may be revealed, raising potential clinical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it cannot be excluded that DDIs predicted to be moderate in SARS-CoV-2-uninfected patients might eventually become clinically relevant in some phases of the COVID-19 disease. Indeed, during the active phase of SARS-CoV-2 infection, pro-inflammatory cytokines are likely to downregulate the activity of liver enzymes, eventually counterbalancing the well-known inductive effect of corticosteroids on drug metabolism [ 9 ]. However, when the inflammatory phase ends, corticosteroid-related DDIs may be revealed, raising potential clinical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there are 57 isoforms of human CYP enzymes that are responsible for the biotransformation of endobiotic and xenobiotic substances including COVID-19 medications [ 36 ]. CYP3A4 is a critical enzyme that is responsible for about 70% of the drugs available in the clinic [ 37 ]. However, there are additional major CYP enzymes including CYP2C9, CYPC19, CYP2C8, CYP2D6, and CYP1A2 [ 35 ].…”
Section: Potential Drug-drug Interactions Involving Remdesivirmentioning
confidence: 99%
“…In terms of CYP-related interactions with remdesivir, there are ample opportunities of modulating remdesivir metabolism due to the CYP inducers and inhibitors administered in COVID-19 patients [ 37 ]. Though CYP3A4 is reported to have about 10% contribution in the metabolism of remdesivir [ 65 ], depending on the relative status of non-CYP metabolizing enzyme activities, CYP3A4 may contribute to a higher extent.…”
Section: Potential Drug-drug Interactions Involving Remdesivirmentioning
confidence: 99%
“…This indicated that remdesivir PK profile could be variable depending on the status of the COVID-19 patients. Several clinical studies have suggested that liver and renal functions are potential compromised during the severe COVID-19 which can alter remdesivir PK (1,40,42).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its emergent nature, there are limited treatment options available against the coronavirus disease of 2019 . Treatment regimens against COVID-19 focus on preventing replication of the virus as well as managing inflammation and other symptoms (1). Chloroquine, hydroxychloroquine, azithromycin, ivermectin, and lopinavir/ritonavir have been used as treatment options against COVID-19 (2).…”
Section: Introductionmentioning
confidence: 99%